Altered nociception in Alzheimer disease is associated with striatal-enriched protein tyrosine phosphatase signaling. Issue 6 (June 2021) - Lee, Zhung-Fu; Huang, Tzu-Hsuan; Chen, Shih-Pin; Cheng, Irene Han-Juo
Abstract : Abstract: Alzheimer disease (AD) is the most common form of dementia, accounting for approximately 60% of cases. In addition to memory loss, changes in pain sensitivity are found in a substantial proportion of patients with AD. However, the mechanism of nociception deficits in AD is still unclear. Here, we hypothesize that the nociception abnormality in AD is due to the aberrant activation of striatal-enriched protein tyrosine phosphatase (STEP) signaling, which modulates proteins related to nociception transduction. Our results indicated that the transgenic mice carrying human amyloid precursor protein (APP) gene had lower sensitivity to mechanical and thermal stimulation than the wild-type group at the ages of 6, 9, and 12 months. These APP mice exhibited elevated STEP activity and decreased phosphorylation of proteins involved in nociception transduction in hippocampi. The pharmacological inhibition of STEP activity using TC-2153 further reversed nociception and cognitive deficits in the APP mice. Moreover, the phosphorylation of nociception-related proteins in the APP mice was also rescued after STEP inhibitor treatment, indicating the key role of STEP in nociception alteration. In summary, this study identifies a mechanism for the reduced nociceptive sensitivity in an AD mouse model that could serve as a therapeutic target to improve the quality of life for patients with AD. Abstract : Supplemental Digital Content is Available in the Text.Alzheimer disease mouse model has decreased sensitivity to noxious stimuli. This deficit is associated with the abnormal increase of striatal-enriched protein tyrosine phosphatase activity in the brain.